PROCESS OF E-RECRUITMENT FOR ENTRY LEVEL POSITIONS IN NORTH MACEDONIA - Kiselichki, Martin; Josimovski, Saso; Pulevska ivanovska, Lidija (Faculty of Economics-Skopje, Ss. Cyril and Methodius University in Skopje, 2022)
The focus of the paper are the different channels for implementation of e-recruitment and their respective efficiency. As the “work from home” model became the default in the pandemic, there was a steady rise in the use of e-recruitment platforms and social media channels. However, businesses report that there is a discrepancy between in the e-recruitment process between varying position levels, based on the industry, type of job and required experience. The paper researches the first step (i.e. attracting candidates) in the e-recruitment process for entry-level positions, as defined being with lower than country average salary, no required experience and faculty education. Through the process of primary quantitative and qualitative analysis, the results of the paper determine that certain channels may deliver results several times higher than others, in particular social media as a whole. Variable factors such as creative elements, job description and other are outlined in the paper to place the foundation for further research. The reach and efficiency of social media channels in e-recruitment is determined to be a powerful tool if utilized within a proper framework. The paper finalizes the research with the obstacles created with e-recruitment as a whole in the recruitment process, after the first phase of attracting candidates is completed.
Keywords: e-recruitment, social media recruitment, job ads, attracting candidates